Comparison of multiple treatment regimens in children with Helicobacter pylori infection: A network meta-analysis - Liang, Miaomiao; Zhu, Chengbi; Zhao, Peipei; Zhu, Xiaohui; Shi, Junwei; Yuan, Bin (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Multiple regimens have been widely used in the eradication treatment of Helicobacter pylori infection in children. However, there is a lack of comparison and evaluation of their effectiveness in different regions of the world. Methods: Randomized controlled trials were retrieved. Review Manager 5.4, Stata SE 15 and R language 4.0.4 were used to analyze date. The ranking probability is assessed according to the surfaces under cumulative ranking (SUCRA). Results: 163 studies were eligible for this study, involving 336 arms and 18,257 children, and 10 different interventions. The results showed that the eradication rates of Sequential therapy with probiotics (SP), Bismuth-containing quadruple therapy, Concomitant therapy and Standard triple therapy (PCN) were at least 90%. Cumulative ranking showed that SP therapy had the best eradication effect (SUCRA 92.7%) whereas Bismuth-containing triple therapy (B) had the worst (SUCRA 3.5%). Subgroup analysis suggested that SP therapy ranked first in China and other regions, and the ranking of Triple therapy with probiotics therapy (TP) was equally stable (SUCRA 72.0% vs 76.4% respectively). The security of the SP and TP therapy had great advantages. Conclusions: As for the eradication treatment of Helicobacter pylori infection in children, SP therapy ranks highest. SP and TP therapies are most safe.